2017
DOI: 10.1002/app.44775
|View full text |Cite
|
Sign up to set email alerts
|

Morphologies and mechanical properties of polyethersulfone modified epoxy blends through multifunctional epoxy composition

Abstract: Thermoplastic polyethersulfone (PES) modified multifunctional tetraglycidyl-4,4 0 -diaminodiphenylmethane (TGDDM) and triglycidyl para-aminophenol (TGAP) epoxy prepolymers cured with 4,4 0 -diaminodiphenylsulfone (44DDS) were prepared using a continuous reactor method and their reaction-induced phase separated morphologies and mechanical properties were measured and correlated with chemical compositions. 1 H nuclear magnetic resonance ( 1 H NMR) and near-infrared spectroscopy (NIR) were used to quantify the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…It is important to note that the end‐group of the PES5003P can react with epoxy as studied by Cheng et al [31] and mentioned by Rosetti [13]. Thus an epoxy‐PES block copolymer is formed which is more soluble with epoxy than the PES.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the end‐group of the PES5003P can react with epoxy as studied by Cheng et al [31] and mentioned by Rosetti [13]. Thus an epoxy‐PES block copolymer is formed which is more soluble with epoxy than the PES.…”
Section: Resultsmentioning
confidence: 99%
“…Fernandez et al [35] did not see phase separation on TGDDM/DDM/PES system by SEM but DMA showed a small shoulder on the α‐relaxation peak of the TS which confirmed that phase separation had occurred. Cheng et al studied TGDDM/TGAP/44′DDS/15 wt% PES with OH end‐group through different formulations (along different quantities of each monomer) [31]. Besides no phase separation was seen on SEM, they distinguished nanophases around 50 nm by Atomic Force Microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Although the two systems have similar toughening mechanism including energy consuming as well as preventing crack growth by particle bridging, crack deflection, and crack termination [Figure (a,b)], dimensions of thermoplastic phase will also play an effect on toughening. Specifically, the size of PES phase in m‐PES8/EP is about two times of that in t‐PES8/EP, so m‐PES8/EP has a bigger toughening effect than t‐PES8/EP (Figure ) because island with larger size tends to have a bigger toughening effect …”
Section: Resultsmentioning
confidence: 99%
“…Polymeric matrices used for composite preparation can be classified into two types: thermoplastic and thermoset. Among these, epoxy resin (EP) has become one of the most widely used matrices for fabrication of fiber‐reinforced polymer‐based composites because of its processability, good mechanical performance, chemical resistance, and compatibility with most fibers . However, cured EP has a high sensitivity to external forces, due to its high crosslinking density .…”
Section: Introductionmentioning
confidence: 99%